Oman, a Vital Sea Link in the Silk Road - Madelung, Wilferd (The 9th Conference on Ibadi Studies: China and the World: Development and Cooperation from the Perspective of the Belt and Road Initiative, 2018)

Fazārī, ʿAbdallāh b. Yazīd al- - Madelung, Wilferd (Encyclopaedia of Islam, 2016)
Keywords: Biographies; Fazārī, ʿAbd Allāh ibn Yazīd al-

'Abd Allāh ibn Ibāḍ's "second letter to 'Abd al-Malik" - Madelung, Wilferd (al-Ummah wa-al-dawlah wa-al-tārīkh wa-al-maṣāʼir : dirāsāt muhdāh ilá (Maulānā) Riḍwā al-Sayyid bi-munāsabat bulūghhihi al-sitīn., 2011)

Abd Allah b. Yazid al-Fazari’s Rebuttal of the Teaching of Ibn Umayr - Madelung, Wilferd (Theological Rationalism in Medieval Islam : new sources and perspectives, 2010)
Keywords: Fazārī, ʿAbd Allāh ibn Yazīd al-; Foi -- Traité -- 8e siècle

’Isa ibn ’Umayr’s Ibāḍī Theology and Donatist Christian Thought - Madelung, Wilferd (Medieval Arabic Thought: Essays in Honour of Fritz Zimmermann, 2012)
Keywords: Donatisme; Foi -- Traité -- 8e siècle

The early Ibāḍiyya and the Zaydiyya - Madelung, Wilferd (Ibadism in Islamic medieval societies:Political models, social forms of organization and interaction, 2013)

The authenticity of the letter of ‘Abd Allâh b. Ibâḍ to ‘Abd al-Malik - Madelung, Wilferd (Revue des mondes musulmans et de la Méditerranée, 2012)
The so-called first letter of Ibn Ibâḍ was long considered in modern scholarship as an authentic letter of ‘Abd Allâh b. Ibâḍ, the reputed founder of the Ibâḍiyya sect, to the Umayyad caliph ‘Abd al-Malik. This was questioned first by John Wilkinson and then by Michael Cook in his book on Early Muslim Theology, who proposed that the letter was written rather by Jâbir b. Zayd to the Muhallabid amîr ‘Abd al-Malik b. al-Muhallab. In his recent book on Ibadism, John Wilkinson has argued that the letter was addressed to ‘Abd al-Malik, the son of the caliph ‘Umar II, and that Jâbir b. Zayd could not have been its author. It will be argued in this paper that the letter is an authentic letter of ‘Abd Allâh b. Ibâḍ addressed to the son of ‘Umar II. Ibn Ibâḍ was not the founder of the Ibâḍiyya sect, but rather a contemporary and rival of Abû ‘Ubayda Muslim b. Abî Karîma.

The progress of the joint project to edit and publish all extant early Ibāḍī texts in a critical edition - Madelung, Wilferd (Ibadism and the Study of Islam: A view from the edge, 2019)

Ibāḍiyya - Madelung, Wilferd (The Oxford Handbook of Islamic Theology, 2016)

Some Reflexions on the Origins of the Ibāḍiyya and Zaydiyya - Madelung, Wilferd (L’ibadisme dans les sociétés de l’Islam médiéval, 2018)

Ibāḍiyya and Mu‘tazila: Two Moderate Opposition Movements in Early Islam - Madelung, Wilferd (Ibadi theology: rereading sources and scholarly works, 2015)

ʿAbd Allāh b. al-ʿAbbās and the Muḥakkima - Madelung, Wilferd (Today's perspectives on Ibadi history, 2017)

Al-Haytham b. 'Adī on the offences of the Caliph 'Uthmān - Madelung, Wilferd (Proceedings of the 23rd Congress of L’Union Européenne des Arabisants et Islamisants : Centre and Periphery within the borders of Islam, 2012)

‘Abd Allāh Ibn Yazīd al-Fazārī on the Abode of Islam - Madelung, Wilferd (On Ibadism, 2014)
Keywords: Fazārī, ʿAbd Allāh ibn Yazīd al-; Foi -- Traité -- 8e siècle

John C. Wilkinson, Ibâḍism: Origins and Early Development in Oman, Oxford Oriental Monographs (Oxford, U.K.: Oxford University Press, 2010). Pp. 500. $185.00 cloth. - Madelung, Wilferd (International Journal of Middle East Studies, 2012)
Keywords: Recension

كتاب الأكلة وحقائق الأدلة: والمذهب الإباضي في عمان - Madelung, Wilferd (مجلة المسار, 2017)

Ibāḍī texts from the 2nd/8th century - Salimi, Abdulrahman al-; Madelung, Wilferd (Islamic History and Civilization, 2018)
In 'Ibāḍī Texts from the 2nd/8th Century' Abdulrahman Al-Salimi and Wilferd Madelung present an edition of fourteen 'Ibāḍī' religious texts and explain their contents and extraordinary source value for the early history of Islam. The 'Ibāḍīs' constitutes the moderate wing of the Kharijite opposition movement to the Umayyad and ʿAbbasid caliphates. The texts edited are mostly polemical letters to opponents or exhortatory to followers by ʿAbd Allah b. Ibāḍ, Abu l-ʿUbayda Muslim b. Abi Karima and other Ibāḍī leaders in Basra, Oman and Hadramawt. An epistle detailing the offences of the caliph ʿUthman is by the early Kufan historiographer al-Haytham b. ʿAdi. By their early date and independence of the mainstream historical tradition these txts offer the modern historian of Islam an invaluable complement to the well-known literary sources
Keywords: Sources -- Ibadisme

Kitāb al-Akilla of Qāḍī Najjād b. Mūsā l-Manḥī and the Ibāḍī Creed in Oman - Madelung, Wilferd (Local and global Ibadi identities, 2019)

Aqwāl Qatāda and the Shuʿaybiyya and Nukkār - Madelung, Wilferd (Ibadi jurisprudence: origins, developments and cases, 2015)
Keywords: Nukkarisme

Al-Salimi, Abdulrahman / Madelung, Wilferd: Early Ibāḍī Literature. 2011. - Rebstock, Ulrich (Orientalistische Literaturzeitung, 2017)
Keywords: Recension

Review of Early Ibāḍī Literature. Abu l-Mundhir Bashīr b. Muḥammad b. Maḥbūb. Kitāb al-Raṣf fi l-Tawḥīd, Kitāb al-Muḥāraba and Sīra. (Abhandlungen für die Kunde des Morgenlandes, 75) - Prevost, Virginie (Wiener Zeitschrift für die Kunde des Morgenlandes, 2012)
Keywords: Recension

Religion and Politics in Ibāḍism: A Historical Survey - Madelung, Wilferd (Oman, Ibadism and modernity, 2018)

Early Ibāḍī Theology : Six kalām texts by ʿAbd Allāh b. Yazīd al-Fazārī, written by Abdulrahman al-Salimi and Wilferd Madelung - Aillet, Cyrille (Arabica, 2017)
Keywords: Fazārī, ʿAbd Allāh ibn Yazīd al-; Recension

Review of Early Ibāḍī Theology. Six kalām texts by ʿAbd Allāh b. Yazīd al-Fazārī. (Islamic History and Civilization 106) - Thiele, Jan (Wiener Zeitschrift für die Kunde des Morgenlandes, 2016)
Keywords: Fazārī, ʿAbd Allāh ibn Yazīd al-; Recension

Abdulrahman Al-Salimi and Wilferd Madelung (eds): Ibāḍī Texts from the 2nd/8th Century. (Islamic History and Civilization. Studies and Texts 133.) vi, 392 pp. Leiden: Brill. 2018. €110. ISBN 978 90 04 33064 1. - Gaiser, Adam R. (Bulletin of the School of Oriental and African Studies, 2018)
Keywords: Recension

AL-SALIMI, A., and W. MADELUNG (eds.) — Early Ibadi Literature. Abu l-Mundhir Bashir b. Muhammad b. Mahbub, Kitab al-Rasf fi l-Tawhid, Kitab al-Muharaba and Sira - Custers, Martin H. (Bibliotheca Orientalis, 2012)
Keywords: Recension

Early Ibāḍī Literature: Abu l-Mundhir Bashīr b. Muḥammad b. Maḥbūb Kitāb al-Raṣf fi l-Tawḥīd, Kitāb al-Muḥāraba and Sīra, by Abdulrahman al-Salimi and Wilferd Madelung (eds.) - Gaiser, Adam R. (Ilahiyat Studies, 2010)
Keywords: Recension

MADELUNG, W., and A. AL-SALIMI (eds.) – Ibāḍī Texts from the 2nd/8th Century. (M.H. Custers) - Custers, Martin H. (Bibliotheca Orientalis, 2019)
Keywords: Recension

Abdulrahman Al-Salimi and Wilferd Madelung: Early Ibāḍī Theology: Six kalām Texts by ‘Abd Allāh B. Yazīd Al-Fazārī. (islamic History and Civilization.) Cvi, 241 Pp. Leiden: Brill, 2014. €99. Isbn 978 90 04 27025 1. - Gaiser, Adam R. (Bulletin of the School of Oriental and African Studies, 2015)
Keywords: Fazārī, ʿAbd Allāh ibn Yazīd al-; Recension

ʿAbd Allāh b. Yazīd al-Fazārī’s Rebuttal of the Teaching of Ibn ʿUmayr - Madelung, Wilferd (Theological rationalism in medieval Islam: new sources and perspectives, 2018)
Keywords: Fazārī, ʿAbd Allāh ibn Yazīd al-; Foi -- Traité -- 8e siècle

Ibāḍī Texts from the 2nd/8th Century - Love Jr, Paul M. (Al-Masāq, 2019)
Keywords: Recension

Early Ibāḍī Literature: Abu l-Mundhir Bashīr b. Muḥammad b. Maḥbūb Kitāb al-Raṣf fi l-Tawḥīd, Kitāb al-Muḥāraba and Sīra - Ibn Maḥbūb, Bashīr ibn Muḥammad (Abhandlungen fur die Kunde des Morgenlandes, 2011)
Keywords: Foi -- Traité

Early Ibāḍī theology: six kalām texts - Fazārī, ʿAbd Allāh ibn Yazīd (Islamic History and Civilization, 2014)
Keywords: Fazārī, ʿAbd Allāh ibn Yazīd al-; Foi -- Traité -- 8e siècle